Controle interno do poder executivo federal : um estudo de caso da Controladoria-Geral da União (2001 - 2017) - Beatriz Silva da Costa (2020)
How did the institutional construction of the Brazilian Office of the Comptroller General take place in the context of Brazilian coalition presidentialism? This case study seeks to answer this question by analyzing the institutional designs of the CGU with initiatives from the Executive Power that have been processed in the legislative arena. This work is part of a research agenda aimed at understanding the internal dynamics of the Executive Branch in the light of three main theories: principal-agent, legislative review and design of agencies. According to the political control literature, the Executive is expected to take action to design the CGU as an institutional mechanism for intra-executive control of the coalition. On the other hand, the legislature and/or coalition parties are expected to act to moderate/reduce/neutralize the use of this instrument to limit the performance of parties in the Executive. In order to analyze the executive-legislative relationship, we identified the strategies adopted by the Executive in the Legislative and the latter's reactions to such proposals. The results of this work indicate that the Legislature was, in the main, favorable to the initiatives of the Executive Power with regard to the proposals for the administrative design of the CGU. Although the Legislative carried out minor interventions within the scope of the Executive's proposals, all the opinions that evaluated the Provisional Presidential Decree were favorable. The results also point out that the heterogeneity of the coalition is not a factor that drives many changes in the CGU that aim at greater intra-executive control. Without much significant variation in administrative design, CGU became institutionalized during the 18 years analyzed and maintained two agency standards.